2017
DOI: 10.3389/fmicb.2017.02113
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Prunus sogdiana NBS-LRR Subgroup Gene PsoRPM2 Promotes Resistance to the Root-Knot Nematode Meloidogyne incognita in Tobacco

Abstract: Root-knot nematodes (RKNs), particularly Meloidogyne incognita, are the most devastating soil-borne pathogens that significantly affect the production of Prunus spp. fruit. RKN infection is difficult to control and consequently causes massive yield losses each year. However, several germplasms of wild Prunus spp. have been shown to display resistance to M. incognita. Consequently, both the isolation of novel plant resistance (R) genes and the characterization of their resistance mechanisms are important strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…As intracellular receptors, NBS-LRR proteins could bind pathogen effectors directly or indirectly through perceiving effector-induced modifications to other proteins, inducing host defense responses (Eitas and Dangl, 2010;Li et al, 2015). To date, numerous NBS-LRR genes have been reported to be involved in resistance to pathogens (Axtell and Staskawicz, 2003;Mackey et al, 2003;Shao et al, 2003;Cherkis et al, 2012;Jun et al, 2016;Macqueen et al, 2016;Zhu et al, 2017). However, functions of NBS-LRR genes in the wheat HTSP to Pst remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As intracellular receptors, NBS-LRR proteins could bind pathogen effectors directly or indirectly through perceiving effector-induced modifications to other proteins, inducing host defense responses (Eitas and Dangl, 2010;Li et al, 2015). To date, numerous NBS-LRR genes have been reported to be involved in resistance to pathogens (Axtell and Staskawicz, 2003;Mackey et al, 2003;Shao et al, 2003;Cherkis et al, 2012;Jun et al, 2016;Macqueen et al, 2016;Zhu et al, 2017). However, functions of NBS-LRR genes in the wheat HTSP to Pst remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Using high throughput VIGS assay, Hsp90 was characterized to be a cofactor of Rx protein to stabilize its protein level ( Lu et al, 2003 ). Association of Hsp90 with NBS-LRR proteins has been reported ( Hubert et al, 2003 ; Liu et al, 2004 ; Zhu et al, 2017 ). Hsp90 associates with N protein directly to modulate the immune response to TMV ( Liu et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90, SGT1 and Rar1 form a complex and act as co-chaperones during virus disease resistance ( Picard, 2002 ). In fact, the structurally conserved Hsp90-SGT1 complex ( Seo et al, 2008 ; Shirasu, 2009 ) are functionally required for different NBS-LRR proteins’ function as immune modulator against various pathogens including bacteria ( Takahashi et al, 2003 ; Zhang et al, 2004 ), fungi ( Bieri et al, 2004 ; Thao et al, 2007 ), oomycetes ( Michael Weaver et al, 2006 ; Bhaskar et al, 2008 ; Oh et al, 2014 ), nematodes ( Bhattarai et al, 2007 ; Zhu et al, 2017 ). Here we reported that Hsp90 directly interacts with Tm-2 2 , a CC-NBS-LRR type of resistance protein, confers robust immune response against tobamoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing the HSP90 in tomato, increased the number of eggs and galls in tomato plants exposed to M. javanica [61]. As well as, it was demonstrated that the PsoRPM2 gene coding a TIR-NB-LRR-type protein in Tobacco has high expression levels in presence of M. incognita, it was also observed that PsoRPM2 gene interacted with the HSP90 protein [62]. Furthermore, several Hsp20 proteins in soybean were reported as differentially expressed in PI 595099 and cv.…”
Section: Expression Analyses Of Candidate Genes For Resistance To M mentioning
confidence: 92%